Introduction of Water Treatment in Slot‐Die Coated Organic Solar Cells to Improve Device Performance and Stability. (23rd June 2022) - Han, Nara; Heo, Youn‐Jung; Lee, Minwoo; Moon, Yina; Yang, Dongseong; Kim, Yunseul; Kim, Dong‐Yu
Abstract: Recent advances in the development of organic solar cells (OSCs) have produced power conversion efficiency (PCE) of over 19%. Various studies have been conducted on scalable coating methods that are compatible with large‐area production of organic photovoltaic modules. However, it is still difficult to control the bulk heterojunction (BHJ) morphology of the active layer during large‐scale fabrication of OSCs. This study reports a morphology‐controllable strategy in OSCs using water treatment (WT) in the stirring process of the active solution, thus resulting in vortex agitation. The effects of WT and water injection volume are investigated based on three reference cells for the optimization of small‐ and large‐area devices, and the physicochemical and optical properties of the films are compared with those without WT. The thin films with WT exhibit a smoother morphology than those without WT, indicating well‐dispersed donor–acceptor phases. Therefore, enhanced efficiencies of the films are achieved via WT. Furthermore, large‐area solar cell modules with a total effective area of 10 cm 2 are fabricated, and they exhibit superior PCEs as high as 11.92% (H‐NF‐DIW10), indicating that the WT method is a simple and effective strategy to fabricate large‐area organic photovoltaic modules. Abstract : The introduction of water treatment during the stirring process of the active solution produces organic solar cells (OSCs) with improved device efficiency and stability. In small‐ and large‐active‐area devices, good dispersion of the donor and acceptor phases can improve charge dissociation, transport, and collection. Thus, water treatment is useful for the commercialization and improvement of large‐area OSCs.